The effect of water in THF/water mixtures on CMC, aggregation sizes, and fluorescence quenching of a new calix[4]resorcinarene macrocycle - Sosa, María Virginia (2024)
This study explores how water content modulates the self-assembly and fluorescence behavior of a novel calixarene, C1. C1 forms large, flattened structures in pure THF, but water addition triggers a transition to smaller, unimodal clusters. A critical micellar concentration (CMC) is identified, decreasing with increasing water content. Fluorescence quenching is observed upon water addition, attributed to nonradiative deactivation. These findings highlight water as a key regulator of C1's assembly and fluorescence, paving the way for further development of water-responsive calixarene systems.